Новые пустынные род и вид пилильщиков-эмпириин (Hymenoptera, Tenthredinidae) из Монгольской Народной Республики - Ермоленко, В.М. (Вестник зоологии, 1968)
The article deals with a description of a new desert monotypical genus and new species of the family Tenthredinidae — Mongolempria zhelochovtsevi Ermoienko, sp. n. (tribe Empriini) from Mongolia. Adult individuals of Tenthredinidae (12m, 12f) are found on the bushes of blossoming desert plant — Calligonum mongolicum Turcz., which grows on bare bald sands of desert — the Alashanskaya Gobi. The species des-cribed is an endemic of the desert fauna in the Central Asia.